ANALYSIS OF TRADE TURNOVER, THE BELT AND ROAD INITIATIVE, AND TECHNOLOGY TRANSFER BETWEEN CHINA AND UZBEKISTAN (Лучшие интеллектуальные исследования, 2025)
This study examines the economic relationship between China and Uzbekistan, focusing on trade turnover, the Belt and Road Initiative (BRI), and technology transfer. Employing a mixed-methods approach, including statistical analysis, case studies, and policy reviews, the research analyzes data from 2017 to 2025 to identify trends, impacts, and opportunities. Results indicate a significant increase in trade volume, driven by BRI-related infrastructure projects, a growing role of Chinese investments in Uzbekistan’s economy, and advancements in technology transfer in sectors like telecommunications and renewable energy. The discussion highlights mutual benefits, challenges, and policy recommendations to enhance sustainable cooperation. This study underscores the strategic importance of these dimensions in strengthening China-Uzbekistan relations, offering insights for policymakers and researchers.